Framework on core competences for physiotherapists and nurses working with older adults in Sri Lanka - Pereira, D.; Senanayake, K.; Jayawardana, S.; Santhalingam, S.; Kamalarupan, L.; Tha- botharan, D.; Sujendran, S.; Lokeesan, V.; Karthijekan, K.; Senavirathna, C.; and et, al (RIAGE, 2025)
The popula*on of Sri Lanka is rapidly ag- ing, and there is a growing demand for healthcare professionals skilled in older adult’s care. The CAPAGE project “Promot- ing academic and professional excellence in health care to meet the challenges of ag- ing in Sri Lanka” is a transna*onal Euro- pean Union co-funded project to enhance professional competences of health care professionals. The main objec*ve of this study is to create a framework of core com- petences for physiotherapists and nurses working with older adults in Sri Lanka. Based on a recent literature review and a focus group analysis with experts, a com- petences framework will iden*fy knowledge and skill-based competences required for health care professionals, spe- cifically for physiotherapists and nurses, working with elderly. Main competences iden*fied were: high-quality standards and team leadership (leader/expert); pa*ent- centered prac*ce, effec*ve communica- *on (communicator); interprofessional ef- fec*ve team collabora*on and shared deci- sion-making process (collaborator); coor- dina*on of care and healthcare manage- ment (organizer); health promo*on, well- ness and well-being (health and welfare advocate); evidence-based prac*ce and lifelong learning and con*nuous profes- sional development (scholar); professional and ethical standards and mul*-dimen- sional approach and best prac*ces (profes- sional). This framework on competences can enable to update and improve knowledge, know-how, skills and mainly the conceptual approach in care and man- agement of older adults, considering specific socio-economic and cultural as- pects of Sri Lanka.
Keywords: Competences; Sri Lanka; Older Adults; Nursing; Physiotherpy